Healthy housing, sustainable city and interlocution between science and society - Mendes, Élgen Soares; Sígolo, Letícia Moreira; Toledo, Renata Ferraz de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
COVID-19 provided important reflections about the organization of cities and housing, its influence on health and the need for us to act towards the construction of a more sustainable world with fewer inequalities. This paper aimed at analyzing the relationship between health, housing and sustainability, and how these themes are interconnected and related to the Sustainable Development Goals (SDG) set forth in the 2030 Agenda. This is a study of a theoretical and conceptual nature with a qualitative approach, conducted by means of a bibliographic review. The analysis of 15 articles selected enabled the elaboration of three categories: the first addresses the housing-health connection; the second, in a more macro scale, analyzes the relationship between city, health and sustainability; and the third highlights the relevance of participative processes to strengthen public policies. The relevance of analyzing the ‘health of housing and cities’ in an interdisciplinary and intersectoral way was evidenced, considering the various environmental, social, cultural, economic and political determinants, among others, and their connections towards sustainability, and health as cross-sectional to all SDGs, which requires strengthening of healthy public policies. It is ethically imperative to create and expand spaces for dialog to qualify public policies in the interface of the health, environment and urban planning areas, as well as to face situations of socio-environmental vulnerability and health inequalities. The current scenario of the COVID-19 pandemic reinforces this evidence and requires greater approximation between science, politics and society.